207k views
1 vote
The expression (5b3c−6)−1(5b−2a−4)−1

(
5
b
3
c

6
)

1
(
5
b

2
a

4
)

1
equals na^rb^sc^t
n
a
r
b
s
c
t

The expression (5b3c−6)−1(5b−2a−4)−1 ( 5 b 3 c − 6 ) − 1 ( 5 b − 2 a − 4 ) − 1 equals-example-1

2 Answers

4 votes

Answer: its 7

Explanation:

User Ziggy
by
6.4k points
2 votes


(5b^3c^(-6))^(-1)(5b^(-2)a^(-4))^(-1)\\\\\text{use:}\ (ab)^n=a^nb^n\\\\=5^(-1)(b^3)^(-1)(c^(-6))^(-1)\cdot5^(-1)(b^(-2))^(-1)(a^(-4))^(-1)\\\\\text{use:}\ (a^n)^m=a^(nm)\ \text{and}\ a^(-1)=(1)/(a)\\\\=(1)/(5)b^(-3)c^6\cdot(1)/(5)b^2a^4\\\\\text{use associative property}\ (a\cdot b)\cdot c=a\cdot(b\cdot c)\\\\=\left((1)/(5)\cdot(1)/(5)\right)a^4(b^(-3)b^2)c^6\\\\\text{use:}\ a^n\cdot a^m=a^(n+m)\\\\=(1)/(25)a^4b^(-1)c^6\\\\Answer:\\n=(1)/(25)\\\\r=4\\\\s=-1\\\\t=6

User Scully
by
5.9k points